Micromachined polymer electrolyte membrane and direct methanol fuel cells : a review - Nguyen, Nam-Trung (2012)
This review reports recent progress of the development of micromachined membrane-based fuel cells. The review first discusses the scaling law applied to this type of fuel cells. Impacts of miniaturization on the performance of membrane-based fuel cells are highlighted. This review includes only the two most common micro fuel cell types: proton exchange membrane micro fuel cells (PEMμFC) and direct methanol micro fuel cell (DMμFC). Furthermore, we only consider fuel cells with active area of a single cell less then one square inch. Since the working principles of these fuel cell types are well known, the review only focuses on the choice of material and the design consideration of the components in the miniature fuel cell. Next, we compare and discuss the performance of different micro fuel cells published recently in the literature. Finally, the review gives an outlook on possible future development of micro fuel cell research.